REFLECTION ON INDONESIA'S DEVELOPMENT FOUNDATION TOWARDS REGIONAL ECONOMIC AWAKENING AFTER THE COVID-19 PANDEMIC IN THE CITY OF SURABAYA - Suyono, Suyono; Susila, Budi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This research was motivated by the decline in Household Consumption Expenditure (PK-RT) caused by the government's policy on PSBB (Large-Scale Social Restrictions), in order to prevent/break the chain of transmission of the Covid-19 Virus. So that it can be formulated in this study how the economic reaction in the community after its activities were limited due to the Covid-19 pandemic. Looking at the phenomena that exist in Indonesia in general and in the city of Surabaya in particular, it is necessary to research the reflection of the foundation of Indonesia's development towards the revival of the regional economy after the COVID-19 pandemic in the city of Sueabaya. The purpose of this study is to analyze the reflection of Indonesia's development foundation towards regional economic revival after the COVID-19 pandemic in the city of Surabaya. This study uses descriptive qualitative methods, empirical studies/literature studies with secondary data sourced from: book documents, scientific articles, regulations, and related ministry/institutional websites. Secondary data of descriptive qualitative approach research with six hypotheses were formulated and tested using regression analysis. Meanwhile, qualitative analysis is taken from the interpretation of the data by providing information and explanations. And empirical studies from the results of previous studies that are relevant/similar. The results showed that from several factors, including: easing PSBB by: lifting of operational restrictions on MSMEs/street vendors, opening tourism destinations, opening airports, KAI operations, opening malls, extended operating hours for street vendors.